(untitled) (Patan Prospective Journal, 2024)
The problem of waste is emerging in the growing cities of Nepal. Waste management has become a serious environmental and public health issue for most local governments of Nepal. This paper assesses the status of solid waste management in Jeetpursimara Sub Metropolitan City (JSSMC) in southern Nepal focusing on waste generation patterns, management practices, and institutional capacities. The major sources of waste in JSSMC were households, business, industries, and health and education institutions. The per capita household waste generation and the total municipal solid waste generation was found to be 125 g/day and 14.92 tons/day (5445.8 tons/year) respectively. The organic waste was found to be in majority (56%) and the rest to be inorganic in nature. JSSMC doesn’t manage the municipal waste directly but has made a contract with the private company that provides municipal services such as sweeping and also a collection of wastes from households and commercial areas. The city lacks a transfer station, and the collected waste is transported directly to the dumping site. At the dumping site, recycling activities are carried out, but the amount of waste recycled is relatively low, representing only 15-20% of the total waste collected. The annual average expenditures of waste management were observed to be USD 67,800. The development of a well managed waste treatment facility has been recommended for the proper management of the increasing problem of solid waste.